Pola Komunikasi Pada Istri Pasangan Pernikahan Jarak Jauh - Putra, Aldilla Suwita; , Dra. Zahrotul Uyun, M.Si, Psi (2017)
The phenomenon of long-distance marriage has increased rapidly. As globalization is developing, where economic growth is increasing while each company has a policy of mutated employees outside the city and even abroad, forcing the employee must leave the nearby (wife / girlfriend / children), the problems faced by the wife in living wedding long distance is communication. This study aims to determine patterns of communication on the wife of a married couple distance. The research was done in solo and Pekalongan to five wives who undergo long-distance marriage.The approach used is qualitative. Data were collected by interview. The analysis used content analysis matrix. From the results of the study revealed that the patterns of communication done by the husband wife frequently use the telephone and other communication media (fuel, line, whatsapp, and video calls) on a daily basis. The language used is English Indoneisa, which initiate communications is the husband, in because her husband always wants to hear from his family. All the things that happen to both partners and they talk about children communicating child development, work, family, and economic. Time which they used for communication intense that night at 19:00 pm, when they finished.The duration ± 1 hour talks - ± 2 hours by including children communicate. Communication with the phone and the media effectively to live a marriage relationship long distance for a quick, no hassle and easy in learn. The information conveyed both wife and husband can change the attitude of the pair, in view of what information is received. The wife was not saturated in relation to undergo long-distance marriage, because she would try to accept and understand the state of their partner.